Fabrication of Heat-Resistant and Plastic-Formable Silicon Nitride - Nishimura, Toshiyuki. (NIMS Monographs, 2015)
In this book, improvements in the heat resistance of silicon nitride (Si3N4) ceramics using grain boundary control and in plasticity at high temperatures using grain size control in order to reduce the cost of shaping Si3N4 are described.   The heat resistance of Si3N4 is improved by mixing a slight amount of sintering additive as an impurity into the original material powder. The author presents his findings on the high heat resistance of Si3N4.   The author also develops a new fabrication method for Si3N4 nano-ceramics that produces high plastic formability. The method developed offers two improved points in grinding and sintering processes. The author found that the plastic formability of Si3N4 nanoceramics is dependent on load stress; the results of his research are detailed in this book.